Student activities on internationalization and personality development a practice: Centre For Foundation Studies International Islamic University case study - Hamedon, Siti Rohimi; Ishak, Izdihar (2012)
Internationalization effort is one of the driving forces and challenges for Malaysia Higher education. There is increasing evidence that higher education institutions must also address the basic personal needs of students by providing a comprehensive set of out-of-classroom student activities and programmes designed to enable and empower students to focus more intensely not only on their studies but also on their personal growth and maturation, both cognitively and emotionally the earliest possible to prepare its graduates marketability globally. In higher education institution, foundation level is the initial stage known as the transition period from secondary school years to higher education institution, thetime to nurture their personality growth to prepare them for the degree programme. The vision of International Islamic University (IIUM) is IIICE;Islamization, Integration, Internationalization and Comprehensive Excellence. It aims at producing holistic individuals that thrives in this world and hereafter. Its Students Activities and development Division offers activities and programmes structured for the development of students’ all rounded personality that will equips students the integration betweeniman (faith), Ilm (knowledge) and amal (practical).This paper evaluatesthe role of Students Activities at the Centre for Foundation Studies International Islamic University Malaysia (CFS IIUM)on its internationalization efforts and in nurturing students’ personality development, leadership potential and developing their softskillsin various aspects. It will presentstrategies, issues and challenges to achieve its objectives as university desires it to be. The paper will outline the principles and values upon which pertinent and effective student activities are based.